Limits of Floating Exchange Rates : the Role of Foreign Currency Debt and Import Structure - Towbin, Pascal (IMF Working Papers; Working Paper ;, 2011)
A traditional argument in favor of flexible exchange rates is that they insulate output better from real shocks, because the exchange rate can adjust and stabilize demand for domestic goods through expenditure switching. This argument is weakened in models with high foreign currency debt and low exchange rate pass-through to import prices. The present study evaluates the empirical relevance of these two factors. We analyze the transmission of real external shocks to the domestic economy under fixed and flexible exchange rate regimes for a broad sample of countries in a Panel VAR and let the responses vary with foreign currency indebtedness and import structure. We find that flexible exchange rates do not insulate output better from external shocks if the country imports mainly low pass-through goods and can even amplify the output response if foreign indebtedness is high.